Nilai-nilai Kemanusiaan dalam Pendidikan Berbasis Ismuba Rahmatan Lil-Alamin - Haringun Nur Adha; Djamaluddin Prawironegoro (Journal of Education and Teaching (JET), 2024)
The aim of this research is to examine whether Ismuba's learning aligns with Rahmatan Lil Alamin's education in the humanitarian aspect. Due to the insufficient emphasis on human values at the educational level, exacerbated by an overwhelming focus on learning rather than holistic education, there is a need for an educational platform capable of instilling human values as a comprehensive solution to societal issues. Like Ismuba's approach, which emphasizes the integration of human values, this research adopts a qualitative methodology with a library-based approach to analyze the Ismuba curriculum through the lens of Rahmatan Lil Alamin's educational theory. The research findings demonstrate that the Ismuba curriculum design incorporates the concept of human values advocated in Rahmatan Lil Alamin's education, emphasizing justice, compassion, care, tolerance, harmony, human dignity, equal rights, and utility. As part of Islamic education, Ismuba offers a comprehensive approach to fostering the internalization of human values and rebalancing the educational landscape to encompass more than just academics.